Learner Autonomy in Mechanical Engineering Students: taking it further - Duarte, Marina (2020)
Lifelong learning is crucial in engineering where new fields are constantly emerging. That is why, in engineering, the education that succeeds will be the one that facilitates lifelong learning and self-directed learning. Learning in a self-directed way requires learner autonomy, which is the ability to take charge of one’s own learning, and the will to act and choose independently. The purpose of this research is to check how the use of mixed methods can contribute to the understanding of how the perceptions of some Portuguese engineering students regarding learner autonomy influence the way they engage in curricular activities and perceive the teacher’s role. Results allow insights and conclusions to be drawn, that are only possible with the use of mixed methodologies, with qualitative data being indispensable to understand results provided by quantitative data.